Perancangan Interior Surabaya Science Centre - Sutanto, Natali Deviana (Intra, 2015)
During this rapid development era with its huge development. The education and entertainment world also experience those wide range changes. The recent entertaining site provides less focus on the educational facility. Which is then leads to the situation that it is more and more difficult to find educational supportive entertaining site. As one of the major cities in Indonesia, Surabaya lack of attention to the needs of society in the field of education entertainment. âSurabaya Science Centreâ Interior design is an education entertainment facility which somehow can help the people to develop better in the field of education. The main facilities such as lobby, ticket area, an areas of biologys, earth and space areas, an area of physics, chemistry area, cinema area, cafe, office, and souvenir shop area provided. The concept of âImaginative Lifeâ is the description of the life of the imagination game with the aim of being informative, educative, as well as entertaining. Interior design applied in Surabaya Science Centre is created based on a fun atmosphere, colorful and thematic so that visitors can change their mindset from boring science being fun and amazing.